EVALUATION OF THE ATTACHMENT AND DEVELOPMENT OF RUBBER CLONES (Hevea brasiliensis) PROPAGATED BY GRAFTING IN THE PERUVIAN JUNGLE - Jorge M. Navarro; Alberto Alva Arévalo; Andi Lozano; Celso Misael Alva-Arévalo; Patricia García-Gonzales; Nery Gaona-Jimenez; Juan R. Baselly-Villanueva; Jorge Saavedra-Ramirez; Geomar Vallejos-Torres (Tropical and Subtropical Agroecosystems, 2024)
Background. The latex yield in Hevea brasiliensis trees is highly variable; Therefore, it is important to propagate commercial clones of this species by grafting in order to standardize or improve latex yields and therefore improve the economic income of producers in this part of the Amazon region. Objective. To evaluate the attachment and development of rubber clones propagated by grafting in the Peruvian jungle. Methodology. Nine-month-old patterns installed in the field were used. These were grafted with budding rods from the commercial clones TR-1, FX-3864, RRIM-600, IAN-873 and MDF-180. A completely randomized block design was used with five treatments and three blocks with 15 experimental units; each containing 30 repetitions. The data obtained were subjected to analysis of variance and Tukey's multiple range test (p<0.05) and the Kruskal Wallis test. Results. The best results in attachment and number of shoots were obtained in grafts with clone MDF-180 with values of 73.33 % and 7.83 shoots respectively; Regarding days to the appearance of the shoot and length, clone TR-1 presented it with 36.63 days and 27.47 cm; The largest leaf area was presented by the graft with clone IAN-873 with 55.46 cm2, while the highest chlorophyll content was obtained in grafts with clone RRIM-600 with 47.18 SPAD. Implications. More studies are required to establish the quality and adaptability of rubber clones propagated by grafting in different site conditions and establish patterns of tree productivity in a short time; Likewise, it is desired to evaluate the quality and quantity of latex produced by these clones. Conclusions. These results indicate the feasibility of propagating Hevea brasiliensis through shoot grafting in the field, which opens great possibilities for propagating rubber trees with better commercial characteristics, particularly with greater latex production.